Tranexamic Acid Analysis as Ethoxycarbonyl‐tert‐butyldimethylsilyl Derivatives by Gas Chromatography–Tandem Mass Spectrometry. (31st January 2020) - Park, Hyung‐Jin; Lee, Hyeon‐Seong; Seo, Chan; Min, Jeuk; Ji, Moongi; Kim, Youngbae; Choi, Subin; Kim, Doo‐Young; Kim, Jung Dong; Jeong, Do Hyeon; Lee, Wonjae; Paik, Man‐Jeong
Abstract : Tranexamic acid (TA) as a synthetic derivative of lysine is a potent antifibrinolytic drug used to reduce bleeding during surgeries including dental extraction. The efficacy of TA administration in ovarian cancer and melasma has also been reported in a previous study. In this study, the mass spectral data set of TA as ethoxycarbonyl‐tert‐butyldimethylsilyl derivatives was newly constructed by gas chromatography‐tandem mass spectrometry in multiple reaction‐monitoring mode. This analytical method was validated with good linearity ( r  > 0.9988), limit of detection (LOD, 0.22 ng/mL), limit of quantification (LOQ, 0.72 ng/mL), relative standard deviation (1.3 to 4.8%), and relative error (−6.8 to 3.5%) under optimal conditions. The LOD and LOQ were assessed to be lower than other reported methods. Therefore, the present method will be useful for monitoring of TA in the pharmacological and cosmetic fields. Abstract : EOC‐TBDMS derivatization processes of tranexamic acid and MRM chromatograms and electron‐impact mass spectrum of EOC‐TBDMS derivatives of tranexamic acid.